The history and illustration of anatomy in the Middle Ages - (:unkn) unknown (SAGE Publications Ltd, 2013)
This article reviews the influence of key figures on the pictorial representation of anatomy and the evolution of anatomical illustration during the Middle Ages until the time of the Renaissance, based on medical history books, journals and ancient medical books. During the early period in the Middle Ages, most illustrationswere traditional drawings of emblematic nature, oftentimes unrealistic, not only because the precise knowledge of anatomy was lacking but also because the objective was to elucidate certain principles for teaching purposes. Five figure-series that came down to us through ancient manuscripts and textbooks represent the best examples of such traditional illustrations.With the advent of human dissection in the 13th and 14th centuries, a significant transformation in the depiction of anatomy began to project the practice of human dissection, as we see in the works of Mondino de Luzzi, Henri deMondeville and Guido de Vigevano. After the invention of book printing in the second half of the 15th century, the reproduction of books was commonly practised and thewoodcut mademultiplication of pictures easier. Peter of Abano, Hieronymous Brunschwig, Johannes de Ketham, Johannes Peyligk, Gregory Reisch, Magnus Hundt, Laurentius Phryesen and many more included several anatomical illustrations in their treatises that demonstrated the development of anatomical illustration during the later Middle Ages. © The Author(s) 2013.
Keywords: Anatomy; Galen; Gregory Reisch; Hieronymous Brunschwig; History; Illustration; Johannes de Ketham; Johannes Peyligk; Laurentius Phryese; Magnus Hunt; Middle ages; Peter of Abano; Soranus; Vesalius